인계난연제 전처리에 따른 셀룰로스계 중공사 탄소막의 특성분석 - 이수오; Su-oh Lee; 정용식; Yong-sik Chung (한국섬유공학회지, 2019)
This study investigated the effect of phosphorus flame retardant treatment on cellulose-based hollow fiber carbon membranes (HFCMs). The HFCMs were prepared by the pyrolysis of cellulose hollow fiber treated with an (NH 4 ) 2 HPO 4 and polysiloxane emulsion mixture. TGA showed that the HFCMs started to decompose at 150℃ and that the carbon yield increased by 9.2% at 850℃. The HFCMs did not show typical cellulose crystalline peaks at 350℃ in XRD analysis. The flexibility of the HFCMs decreased as the final pyrolysis temperature increased. (NH 4 ) 2 HPO 4 treatment lowered the degree of flexibility of the HFCMs. The tensile strength and tensile modulus increased with the pyrolysis temperature.